Friday

March 27, 2015

March 27, 2015

Posted by **Katie** on Monday, October 1, 2012 at 1:30pm.

- algebra -
**Reiny**, Monday, October 1, 2012 at 2:39pmI assume we are solving ??

x^2(3x+1) - 4(3x + 1) = 0

(3x+1)(x^2 - 4) = 0

(3x+1)(x+2)(x-2) = 0

x = -1/3, -2, 2

**Answer this Question**

**Related Questions**

algebra - 24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3...

algebra - 5x -3 = 11 + 12x combine like figures add 3 to both sides to remove ...

Algebra - Can someone please check my work for me. Q: Plot the graph of the ...

algebra - (12x+1)(x-1)=-3 12x^+1=-3 12x^=-1-3 x=1/3 check this problem

Algebra - I'm not sure how to factor 3x^3-12x^2+3x. I tried separatring the 3x ...

algebra2 - 1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators ...

calc - What is dy/dx of y=12/12X-y^3 ???? Any idea anyone??? y=12/12X-y^3 I ...

algebra - Can anyone tell me if I got this problem right 12x-6=11x 12x-6+6=11x+6...

Algebra - What polynomial could you subtract from 5x^3 - 12x - x^2 + 9 - 12x^5...

Algebra 1 - 12 + 12x = 12x + 12 A. None B. one C. Infinitely many D. Two ...